Efficient approach for reliability evaluation of distribution system considering momentary interruption - Ahmed, Tanjil; Hassan, Rezuwan; Ghosh, Palash Chandra; Huq, Mohammad Saiful (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2020.